A study of the process of translating political texts from English to Arabic / Omar Ganim Mohamed - Mohamed, Omar Ganim (2013)
In the international arena, it is a known fact that inaccurately translated political texts can lead to misunderstandings between political leaders and this can strain the relationship between countries or even lead to catastrophic ends. In the world of translation, the translation of political texts from English to Arabic is still not efficient and needs to be improved. Based on this initial finding, the researcher was motivated to investigate the translation of political texts from English to Arabic. The objectives of this study were to (i) investigate the process of translating political texts from English to Arabic which include the strategies and the steps involved in the translation process and, (ii) to identify the problems (such as translation tools, reference materials, organizations, structure of English and Arabic languages, nature of political texts, lack of training and personal development) faced by translators of political texts from English to Arabic in order to understand the real scenario of this kind of translation. A triangulation methodology involving Think-Aloud Protocols (TAPs), interviews and a questionnaire was used. To investigate the internal translation process, five participants took part in the TAPs and another five participants were interviewed. To identify the problems, a survey was carried out using a questionnaire. The questionnaire was administered to 33 participants who are involved in translating political texts from English to Arabic. The analysis of the TAPs was done based on Lorscher’s Model of Discourse Analysis (1991). The theoretical framework for this study comprised the translation strategies put forward by Vinay and Darbelnet (1958), the eight translation strategies by Newmark (1988) and a number of translation models depicting the translation process for example by Bell (1991) and Darwish (2003). The TAPs analysis showed that all the translation strategies put forth by Vinay and Darbelnet (i.e. direct borrowing, literal translation, transposition, modulation, equivalence and adaptation) were used by the respondents except for calque which is a special kind of borrowing. Calque was avoided by the respondents as this strategy had a high tendency of causing difficulties in comprehension in the TL. The highest frequency for the strategy used was equivalence (34%) followed by borrowing (26%). Apart from this, the findings also revealed that the respondents used all of Newmark’s (1988) eight translation strategies (semantic, communicative, functional, literal, neutralization, free, word-for-word and cultural transferring strategy) in the translation process. The highest frequency of use was for functional transfers (87.5%) followed by semantic (62.5%) and communicative transfers (62.5%).The least used strategy was cultural transfer (12.5%). Their translation process also on the whole confirmed that similar steps were taken in translating political texts from English to Arabic as depicted in the translation models by Bell (1991), Darwish (2003) and others. The steps include planning and organizing the translation task, reading, analyzing and comprehending the information in SL text, attending to the text sentence by sentence, translating, checking and revising and evaluating the accuracy of the finished product against the original. The findings from the interview further validated the results of the TAPs analysis. Finally, the findings from the 33 translators’ responses to the questionnaire also revealed that the problems they face during the translation of political texts from English to Arabic rank as follows: passive forms (78%), the variation of tenses for time reference (65%), free speech and expression (63%), terminology (54%), pronunciation and spelling (51%), acronyms (45%), style and concord (35%) and abstractness (28%).